DIFFERENTIATED FORMATIVE FEEDBACK AS A PEDAGOGICAL MECHANISM FOR DEVELOPING SELF-REGULATED LEARNING IN ESP CLASSES (Sciental Journal of Education Humanities and Social Sciences, 2026)
The increasing emphasis on learner autonomy in higher education has intensified the need for pedagogical mechanisms that help students use feedback not merely as correction but as a resource for self-regulated learning. In English for Specific Purposes (ESP) classes, this issue is especially important because students are expected to develop linguistic accuracy, professional vocabulary, genre awareness and communicative confidence within a limited number of classroom hours. This article proposes and theoretically validates a differentiated formative feedback model for ESP instruction. The study follows a design-based pedagogical methodology and integrates principles of formative assessment, feedback literacy, self-regulated learning and ESP pedagogy. The proposed model organizes feedback into three interconnected pathways: diagnostic feedback for identifying learning gaps, dialogic feedback for clarifying meaning and criteria, and feedforward feedback for planning subsequent improvement. The results demonstrate that differentiated formative feedback can create a more transparent learning environment, support students in monitoring their progress and strengthen the connection between teacher guidance, peer interaction and independent revision. The article argues that feedback becomes pedagogically productive when it is timely, criterion-referenced, dialogic and connected to further action. The proposed model may be applied in ESP, technical English and professional communication courses in higher education.